ANALISIS PENGUKURAN DAN PENILAIAN KUALITAS PENERIMAAN SIARAN RADIO FM MENGGUNAKAN FIELD STRENGTH PADA DAERAH SUB URBAN KABUPATEN SANGGAU - ., M.Riski Pratama (Faculty of Engineering, Universitas Tanjungpura, 2019)
Radio Broadcast FM is one of the technology telecommunications used for give away service information and entertainment for society. For reach society listener as targeted consumers, quality reception broadcast to be the very thing crucial . Power emit and propagation from transmitter could influence technical quality service on the recipient. Problem quality this to be the object under study and the approach taken for get results, carried out measurement field with use field strength instruments and plus GPS as determinant accuracy location measurement. Use spectrum radio frequency must corresponding with legislative decisions by Ministry Transportation and not each other disturbing. Use illegal radio frequency could make occurrence disorder that can bring down quality from other radio stations, and harm for station which is on official to be legal user. If seen from results measurement quality reception radio broadcasts in the District Sub- District area Sanggau who use SINPO approach ( Signal, Interference, Noise, Propagation , Overall ), still many area around the border that is experiencing interference, in the form of